Degradation study of polylactic acid/graphene nanocomposites by using accelerated weathering - Nur Fazlinna, Ab Ghani (2023)
One of the most researched biodegradable and biobased polymers is polylactic acid (PLA), which is readily available commercially for a reasonable price and has unique material properties. An aliphatic polyester, PLA has a wide range of essential uses in the packaging, automobile, biomedical, and agricultural industries. Nevertheless, it has some drawbacks, such as brittle in tensile behaviour and poor thermal properties. The introduction of nanofiller improves the polymer matrix's mechanical and thermal properties. Investigating the degrading behaviour of PLA/graphene nanocomposites is the main purpose of this study. The first stage of the study examines the optimum graphene nanoplatelets (GNP) contents of PLA/GNP nanocomposites based on mechanical, thermal, and morphological properties. The second stage is the degradation study of PLA and nanocomposites (i.e., GNP and carboxyl graphene nanoplatelets (GNP‒COOH)) by accelerated weathering technique, including studying the thermal, mechanical and morphological properties of PLA nanocomposites. The PLA/GNP nanocomposite was prepared with various contents of GNP (0, 0.1, 0.3, 0.5, and 1.0 wt%) by melt blending method using a twin-screw extruder. The accelerated weathering was conducted with five different cycles (8, 16, 32, 48, and 64 cycles). The characteristics of the PLA and nanocomposites before and after the accelerated weathering test were analysed by using Field Emission Scanning Electron Microscopy (FESEM), X-ray diffraction (XRD), tensile test, differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and Fourier Transform Infrared Spectroscopy (FTIR) analysis. At low GNP levels, the prepared nanocomposites significantly improved tensile characteristics. The tensile strength of nanocomposites increased considerably when the GNP content in PLA was raised, reaching a maximum value of 50.3 MPa in PLA with 0.3 wt% GNP compared to other compositions. The GNP dispersed uniformly in the PLA/0.3GNP polymer matrix, according to the FESEM results. According to the findings of this study, PLA/GNP nanocomposites with 0.3 wt% GNP had the best mechanical properties of all the formulations tested. The crystallinity of PLA was observed to increase at 0.3 wt% of GNP from 27.0% to 32.7% compared to other compositions. The optimum content of filler at 0.3 wt% was used to study the degradation of PLA and nanocomposites. As a result, the crystallinity of PLA was found to increase up to 50.6% after accelerated weathering. In contrast, the crystallinity of PLA/0.3GNP and PLA/03GNP‒COOH was found to increase at 58.1% and 66.4% after accelerated weathering, respectively. Furthermore, the overall mechanical properties (i.e., tensile strength, Young’s modulus and elongation at break) of the PLA and PLA nanocomposites decreased after accelerated weathering. The leading causes of reduction in the mechanical properties of PLA nanocomposites were found to be water absorption, destruction of nanofiller integrity, degradation of PLA matrix, and formation of cracks and pores. The interface adhesion between the PLA matrix and the GNP and GNP‒COOH is weakened by UV light, moisture, and heat, which causes the nanocomposites to degrade and reduce their mechanical and thermal stability of nanocomposites.